Evaluation of Poly(N-Ethyl Pyrrolidine Methacrylamide) (EPA) and Derivatives as Polymeric Vehicles for miRNA Delivery to Neural Cells - Altea Soto; Manuel Nieto-Díaz; Enrique Martínez-Campos; Ana Noalles-Dols; María Asunción Barreda-Manso; Felipe Reviriego; Helmut Reinecke; David Reigada; Teresa Muñoz-Galdeano; Irene Novillo; Alberto Gallardo; Juan Rodríguez-Hernández; et al. (MDPI AG, 2023)
MicroRNAs (miRNAs) are endogenous, short RNA oligonucleotides that regulate the expression of hundreds of proteins to control cells' function in physiological and pathological conditions. miRNA therapeutics are highly specific, reducing the toxicity associated with off-target effects, and require low doses to achieve therapeutic effects. Despite their potential, applying miRNA-based therapies is limited by difficulties in delivery due to their poor stability, fast clearance, poor efficiency, and off-target effects. To overcome these challenges, polymeric vehicles have attracted a lot of attention due to their ease of production with low costs, large payload, safety profiles, and minimal induction of the immune response. Poly(N-ethyl pyrrolidine methacrylamide) (EPA) copolymers have shown optimal DNA transfection efficiencies in fibroblasts. The present study aims to evaluate the potential of EPA polymers as miRNA carriers for neural cell lines and primary neuron cultures when they are copolymerized with different compounds. To achieve this aim, we synthesized and characterized different copolymers and evaluated their miRNA condensation ability, size, charge, cytotoxicity, cell binding and internalization ability, and endosomal escape capacity. Finally, we evaluated their miRNA transfection capability and efficacy in Neuro-2a cells and rat primary hippocampal neurons. The results indicate that EPA and its copolymers, incorporating β-cyclodextrins with or without polyethylene glycol acrylate derivatives, can be promising vehicles for miRNA administration to neural cells when all experiments on Neuro-2a cells and primary hippocampal neurons are considered together.